Acute Myelogenous Leukemia with the t(7;7)(p15;p22) Translocation, a Novel Simple Variant of t(7;11)(p15;p15) Translocation: First Description - Motoharu Shibusawa (Case Reports in Hematology)
The t(7;11)(p15;p15) translocation is a recurrent genetic abnormality associated with acute myelogenous leukemia (AML). The translocation results in a fusion between the nucleoporin 98 and homeobox genes. We describe a case of AML with t(7; 7)(p15;p22) translocation, which is a novel simple variant of the t(7;11)(p15;p15) translocation. A 66-year-old woman presented with subcutaneous hemorrhage in both forearms. Laboratory test revealed hyperleukocytosis (white blood cell count: 97,800 cells/µL (blasts, 51.0%)), anemia (hemoglobin level: 7.6 g/dL), thrombocytopenia (platelet count: 6.5 × 104/μL), and hyperfibrinolysis (elevated d-dimer level: 12.4 µg/mL; fibrin/fibrinogen degradation products: 26.9 µg/mL). The patient was diagnosed with AML; the blast morphology was unclassifiable according to the French-American-British classification. Flow cytometry CD45 gating revealed that the blasts expressed CD34, CD13, CD33, and CD117. G-banding of tumor cells revealed the t(7;7)(p15;p22) translocation [20/20]. The patient underwent chemotherapy. At 48 days of admission, the patient died of multiple organ failure. The t(7;7)(p15;p22) translocation involved chromosome 7p15, indicating its association with the homeobox genes. To the best of our knowledge, this is the first report of a patient with AML with the t(7;7)(p15;p22) translocation, which is a simple novel variant of the t(7;11)(p15;p15) translocation.